Examining the Effects of Long-Term Study Abroad on the Listenership of Japanese EFL University Students - Pino Cutrone (Cranmore Publishing, 2021)
The purpose of this study is to measure the effect of study abroad on one aspect of learners' pragmatic competence, listenership. A total of 8 Japanese university students participated in this study (4 females and 4 males). Each student was given pragmatic tests at three points in time: within four to seven days of going abroad (pre-test), within seven days of returning to Japan (post-test 1), and approximately eight weeks later (i.e., post-test 2, the delayed post-test). Each of these tests involved participating in an intercultural conversation with a native speaker of English (NES) and being interviewed. To determine the efficacy of preparatory instruction, half of the students set to study abroad (N = 4) were given explicit instruction on listenership. This consisted of two (2-hours each) instructional sessions whereby the teacher drew students' attention to various features of listenership, engaged them in discussions on the implications of cross-cultural communication styles and, subsequently, taught them of some common patterns of listenership in English. The results of this study point to the benefits of long-term study abroad (SA), particularly on the learners who received instruction prior to studying abroad.